Thermodynamics from the S-matrix reloaded, with applications to QCD and the confining Flux Tube - Pietro Baratella; Joan Elias Miró; Emanuele Gendy (Journal of High Energy Physics)
Abstract Over the past decade and more, S-matrix-based calculational methods have experienced a resurgence, proving to be both an elegant and powerful tool for extracting physical quantities without the need for an underlying Lagrangian formulation. In this work, we critically review and further develop the formalism introduced by Dashen, Ma, and Bernstein, which connects the thermodynamics of relativistic systems to the information contained in their scattering amplitudes. As a demonstration, we revisit the computation of the QCD equation of state to leading order in the strong coupling, showcasing the advantages of this method over traditional Thermal Field Theory techniques. Additionally, we apply these tools to the effective theory of a long confining Flux Tube in D dimensions, analyzing thermal effects up to and including NNLO contributions. Our results are compared with those obtained using the Thermodynamic Bethe Ansatz method. We also discuss how these techniques enable the inclusion of non-universal effects in the study of Flux Tubes, while relying solely on the S-matrix as input.